PET/MR Imaging: New Frontier in Alzheimer's Disease and Other Dementias - Zhang, Xin Y.; Yang, Zhen L.; Lu, Guang M.; Yang, Gui F.; Zhang, Long J. (Frontiers in Molecular Neuroscience, 2017)
Alzheimer's disease (AD) is the most common form of dementia; a progressive neurodegenerative disease that currently lacks an effective treatment option. Early and accurate diagnosis, in addition to quick elimination of differential diagnosis, allows us to provide timely treatments that delay the progression of AD. Imaging plays an important role for the early diagnosis of AD. The newly emerging PET/MR imaging strategies integrate the advantages of PET and MR to diagnose and monitor AD. This review introduces the development of PET/MR imaging systems, technical considerations of PET/MR imaging, special considerations of PET/MR in AD, and the system’s potential clinical applications and future perspectives in AD.